Investigating Teaching-Learning Strategies in Improving EFL Learners’ Reading Comprehension: A Lesson Learned from Junior High Schools - Asnawi, Asnawi; Sinaga, Yanti Kristina; Herman, Herman; Sianturi, Beata Klarensya; Kartolo, Rahmat; Tannuary, Arwin (Universitas Pendidikan Mandalika, 2025)
This study investigates the implementation of teaching strategies to improve reading comprehension among eighth-grade students in Indonesian junior high schools, where English is treated as a foreign language. Limited exposure and practice outside the classroom contribute to underwhelming reading proficiency. The research adopts a qualitative case study approach involving two English teachers and eighth-grade students. Data collection methods include observations, interviews, and documentation, while analysis is conducted using Miles and Hubberman’s interactive model. Findings reveal that teachers employ two primary strategies for teaching descriptive text comprehension: Think Aloud and Question Answer Relationships (QARs). The Think Aloud strategy involves guiding students to set reading purposes and make predictions during the pre-reading stage. During reading, students identify key information, resolve unfamiliar vocabulary, and make connections across texts. Post-reading activities include summarizing, evaluating comprehension through performance, and formative assessments. QARs strategy focuses on building background knowledge before reading. Teachers introduce four types of questions – Right There, Think and Search, Author and Me, and On My Own – to guide text interpretation during reading. Reflection and comprehension tests, such as worksheets, are conducted post-reading to assess learning outcomes. The study highlights the effectiveness of interactive and structured approaches in fostering deeper engagement and improving students’ reading comprehension abilities. These strategies offer practical insights for educators seeking to enhance reading proficiency through targeted interventions.